Depression, anxiety and stress among first year medical students in Sylhet division (Bangladesh Journal of Psychiatry, 2024)
Young adulthood is an identity-forming period in which individuals experience social and physical changes as well as conflicts in emotional, behavioral, sexual, economic, academic and social areas. High expectation, burden of vast syllabus, high level of competition, lack of recreational activities, lack of peer support, staying away from home, long working and study hours, sleep deprivation, as well as factors interfering in everyday personal life are common during medical life. So it’s no surprise that, medical students experience high rates of psychological morbidity when compared with students in other disciplines. Objectives of this study was to assess depression, anxiety and stress among 1st year medical students in Sylhet division and find out other correlates. This was a cross sectional study conducted in July 2022 to December 2022 in all the medical colleges of Sylhet division. Among all the students 563 students were consecutively selected as sample; among which 546 retained as sample. A predesigned semi structured questionnaire and Depression Anxiety Stress Scale 21 (DASS 21) were tools for the study. The results showed that, majority of the students were female 338 (62%). Among the participants, 73.8% of students hailed from an urban area, 67.6% students lived in various hostels and 73.1% lived in own home during 12th grade. Most (54.3%) of the students were from government medical college, 80% came from nuclear family, 26.9% reported over protective family, 8.6% had family history of psychiatric illness and 1.6% had illicit drug use history. 28.9% had depression, 37.5% had anxiety and 12.5% had stress.  Significant amount of them had overlapping symptoms and 45 (10.45%) of them had all three psychological domains (anxiety, depression and stress). Majority had moderate level of anxiety 97 (17.8%) whereas mild depression and stress were found in 16.7% and 9.5% respectively.  Depression was significantly associated with sex (p=0.040), anxiety was significantly associated with habitant (p=0.019), residential place (p=0.037) and residence in 12th grade (p=0.028).  Stress was significantly associated with sex (p=0.008). Overprotective family and positive family history of psychiatric illness were significantly associated with depression, anxiety and stress (p=0.005, 0.000, 0.000 and p=0.004, 0.002, 0.002 respectively). This study highlighted importance to look after mental health of students from early medical life, which could ensure future productive doctor and patient satisfaction.Bang J Psychiatry 2023;37(2): 25-31